Sistem Pendidikan Nasional: Akses, Equity, Financing, Monitoring Dan Evaluasi Tinjaun Kajian Literasi - As’ad, As’ad; Suyana, Nana; Jupriadi, Jupriadi; Marhamah, Marhamah (Jayapangus Press, 2024)
The background to this research is the need for sustainable quality evenly throughout Indonesia. Education must also be able to actively develop the potential of students, so that they have religious spiritual strength, intelligence, personality, noble morals and skills that are needed by themselves, society, nation and state. To realize educational goals, it is important to ensure the implementation of four pillars: a) access to education, meaning providing convenience and equal opportunities for everyone to obtain education. Apart from access to education, b) equity means justice in obtaining the same educational opportunities for various groups of society, c) financing, meaning that every citizen is obliged to attend primary and secondary education which must be funded by the government, d) monitoring and evaluation, meaning supervision of policies and evaluation in improving and perfecting policy implementation. The aim of this research is to describe the 4 pillars of education (access, equity, financing and evaluation). The research method uses a literature review, using a literature approach. There were 10 articles studied in collecting data taken from the fields of education, access, equity, financing, monitoring and evaluation. The research conclusion reveals that the success of a country's educational goals is to ensure that the four pillars above run well. Equal rights in education is an important aspect of equality and social justice. It is important to provide financing that has been outlined in the APBN according to the portion of each pillar.